Do Innovative Firms Pay Higher Wages? Micro-Level Evidence from Brazil - Cirera, Xavier (The World Bank, 2020)
Several studies have documented a positive and causal relationship product or process innovation - and labor productivity. Given the links between labor productivity and wages, a likely implication of this positive relationship is that innovation is associated with higher wages of more productive firms. This paper explores the relationship between innovation and wages using Brazil's employer-employee census and a novel measure of innovation derived from the share of technical and scientific occupations of workers in the firm. The results show a robust and positive wage premium associated with innovative firms. The decomposition of this innovation-related wage premium suggests a series of important stylized facts: (i) the innovation wage premium is larger for manufacturing but also positive and significant for agriculture and services; (ii) it is larger for large firms, but also positive and significant for all firm size categories including micro firms; and (iii) it is larger for medium- and low-skill occupations, although this depends on the use of firm fixed effects. More importantly, the paper explores the causality between innovation and wages and finds empirical support for the ideas that "self-selection" firms that innovate already pay higher wages before becoming innovators - and increases in wages associated with starting innovation activity, which are persistent for three years after firms start innovating